2001
DOI: 10.1074/jbc.m102949200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-inducible BCL-3 Expression Is an Autoregulatory Loop Controlling Nuclear p50/NF-κB1 Residence

Abstract: NF-B is a transcription factor whose nuclear residence is controlled by IB family members. In the NF-B-IB autoregulatory loop, activated (nuclear) Rel A⅐NF-B1 induces the resynthesis of IB␣ recapturing nuclear Rel A back into the cytoplasm within 1 h of stimulation. In contrast, NF-B1 subunits redistribute more slowly into the cytoplasm (from 6 to 12 h). Here we examine the role of inducible cytoplasmic BCL-3 expression in terminating nuclear NF-B1. Although BCL-3 is a nuclear protein in B lymphocytes, surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 62 publications
7
93
0
Order By: Relevance
“…Within the BCL3 promoter, two high-affinity NF-kB motifs have been described, located at À872 to À861 and À106 to À96 nt. The latter has been shown to mediate the Transcriptional regulation of BCL3 by IL-6 K Brocke-Heidrich et al upregulation of BCL3 upon TNF-a stimulation in HepG2 cells (Brasier et al, 2001). As mentioned above, the NF-kB site within HS3 was shown to be targeted by stimuli that mimic TCR activation, such as phythaemagglutinin (PHA) and phorbol 12-myristate 13-acetate (PMA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the BCL3 promoter, two high-affinity NF-kB motifs have been described, located at À872 to À861 and À106 to À96 nt. The latter has been shown to mediate the Transcriptional regulation of BCL3 by IL-6 K Brocke-Heidrich et al upregulation of BCL3 upon TNF-a stimulation in HepG2 cells (Brasier et al, 2001). As mentioned above, the NF-kB site within HS3 was shown to be targeted by stimuli that mimic TCR activation, such as phythaemagglutinin (PHA) and phorbol 12-myristate 13-acetate (PMA).…”
Section: Discussionmentioning
confidence: 99%
“…It is itself an NF-kB target gene whose expression is induced by a number of classic NF-kB-inducing stimuli such as tumor necrosis factor-a (TNF-a) (Brasier et al, 2001) or IL-1 (Elliott et al, 2002). Although IL-4 promotes BCL3 transcription in T cells through an AP-1-dependent mechanism (Rebollo et al, 2000), IL-9 was reported to induce BCL3 expression through the Jak/Stat pathway (Richard et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture and Treatment-Human K562 erythroleukemia (16), HepG2 hepatocellular carcinoma (31), and HL-60 acute myeloid leukemia cells stably transfected with BCR-ABL (HL-60/BCR-ABL) or empty vector (HL-60/Neo) were cultured as described (23). Where indicated, paclitaxel (Sigma) was resuspended in Me 2 SO and added to a final concentration of 1 M.…”
Section: Methodsmentioning
confidence: 99%
“…The expression vector encoding the phosphorylation-defective IkBa(S32A/S36A), IkBaM, was a generous gift from Dr Allan R Brasier (University of Texas Medical Branch, Galveston, TX, USA) (Brasier et al, 2001). The expression vectors for IKKb and IKKb-KM (K44A) were generous gifts from Dr Hiroyasu Nakano (Juntendo University, Tokyo, Japan) (Nakano et al, 1998).…”
Section: Transient Transfection Luciferase Assaysmentioning
confidence: 99%